Konsep Waktu Menurut Yusuf Qardhawi; Perspektif Semantik Leksikal - Mitrajati, Kenyo; Musthofa, Tulus; Nasiruddin, Nasiruddin (Study Program of Arabic Language Teaching, 2023)
This research discusses the importance of time written in the Al-Qur'an and Hadith as well as the views of ulama. This research is descriptive qualitative research that explores literature sources that are related to the research problem. This research uses a lexical semantic perspective. The research data is in the form of the term